TINJAUAN TENTANG VARIABEL-VARIABEL CAMEL TERHADAP LABA USAHA PADA BANK UMUM SWASTA NASIONAL - Harianto Respati; Prayudo Eri Yandono (University of Merdeka Malang, 2008)
During the decade of December 2000 to June 2002, banking industry in Indonesiaespecially private general banks had not been able to manage their resource in order to obtainmore profit from their business. The Indonesian Bank had involved in establishing provision ofexecution concerning with financial report, which would be reported to the Indonesian Bankand then it would be published. In such situation, it was important to examine factors whichmight cause the profit to be weakened. This journal consisted of result or research concerningwith the influence of CAMEL variables toward profit of the private national banks. Out offourteen CAMEL variables, there were seven CAMEL variables that had an influence onprofit of the private national banks. ROA variable had more dominant influence than other sixvariables and it proved that during the decade the banking world had been dying and ineffectivein its effort to obtain more profit because of Non performing Loan.